Pendidikan Karakter Masyarakat Lereng Merbabu melalui Budaya Rejeban - Alina Nareswari; Zulkipli Lessy (Mathematics Education Study Program, 2025)
Character education is a vital foundation in the family. How family members will behave in the future when they are involved in society is greatly influenced by the character education that has been instilled. During increasingly advanced times, the people of Merbabu Slope still maintain the Rejeban culture to maintain a cultural heritage that is slowly starting to fade. This article will discuss the role of Rejeban Culture in the character education of the people living on the Merbabu Slopes. This research aims to identify and analyze how this local culture contributes to the character-building of the community. The study used a qualitative approach with data collection techniques through observation and in-depth interviews. The research subjects include community leaders, educators, and residents of Merbabu Slope who actively participate in Rejeban Culture. Rejeban culture is an effective medium in supporting character education of the Merbabu Slope community. The preservation and development of this culture are essential to strengthen positive values in society.